Application of conjoint analysis to the optimum design for fabric printing patterns. Issue 5 (1st August 2019) - Lin, Chiahsu; Wang, Ya-Ching
Abstract : Purpose: The purpose of this paper is to construct the best combination of fabric printing pattern's attributes to obtain the optimum design to meet the markets need. Design/methodology/approach: This study reviewed the morphological analysis of fashion design expert groups regarding the fashionable fabric printing patterns, as well as the attribute preferences for different groups of fabric printing patterns through focus group discussions. In addition, the conjoint analysis was used to calculate the part-worth of these patterns' design attributes and design levels to obtain the optimum design for fabric printing patterns. Findings: The results of this study showed that the most importance of fabric attributes is the secondary pattern (32.59 percent), while the weights of shading element (24.80 percent) and primary pattern (24.46 percent) are almost the same. This study found that a wide range of intertwining image primary pattern can be applied to create interesting and popular fabric printing pattern designs. In practical applications of this result, when the primary pattern is supported by the buyer, fabric designers may use New Classic composite plants, with simple shading and different cycling configuration, to reproduce the optimum designs of the fabric printing patterns. Originality/value: This proposed a novel solution to figure out the combination basis for optimizing fabric printing pattern designs. In addition, this result helps fabric printing pattern designers to establish an optimal design method for a specific brand to create a unique printing pattern design.